"Slalom": Microsurgical Cross-Over Decompression for Multilevel Degenerative Lumbar Stenosis. (18th July 2016) - Mayer, H. Michael; Heider, Franziska
Abstract : Objective. Selective, bilateral multisegmental microsurgical decompression of lumbar spinal canal stenosis through separate, alternating cross-over approaches. Indications . Two-segmental and multisegmental degenerative central and lateral lumbar spinal stenosis. Contraindications . None. Surgical Technique. Minimally invasive, muscle, and facet joint-sparing bilateral decompression of the lumbar spinal canal through 2 or more alternating microsurgical cross-over approaches from one side. Results. From December 2010 until December 2015 we operated on 202 patients with 2 or multisegmental stenosis (115 f; 87 m; average age 69.3 yrs, range 51–91 yrs). All patients were suffering from symptoms typical of a degenerative lumbar spinal stenosis. All patients complained about back pain; however the leg symptoms were dominant in all cases. Per decompressed segment, the average OR time was 36 min and the blood loss 45.7 cc. Patients were mobilized 6 hrs postop and hospitalization averaged 5.9 days. A total of 116/202 patients did not need submuscular drainage. 27/202 patients suffered from a complication (13.4%). Dural tears occurred in 3.5%, an epidural hematoma in 5.5%, a deep wound infection in 1.98%, and a temporary radiculopathy postop in 1.5%. Postop follow-up ranged from 12 to 24 months. There was a significant improvement of EQ 5 D, Oswestry Disability Index (ODI), VAS for Back and Leg Pain, and preoperative standing times and walking distances.